2017
DOI: 10.1515/anre-2017-0008
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index, general fatness, lipid profile and bone mineral density in young women and men

Abstract: AbstrAct:The bone tissue is metabolically active. Throughout the entire life, it undergoes changes in the form of bone resorption processes which are successive, with the participation of the resorbing cells and bone formation processes. The aim of the study was to evaluate mineral density and bone mass tissue and the lipid profile, BMI, total body fat in young females and males. The study involved 100 people (50 females and 50 males) studying in Warsaw at the age of 23,2 ± 4,0 years. The densitometry method o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Based on the age-cutting value of the ROC curve, the majority of subjects were aged >54.50 years (Table 2), which agrees with the study of postmenopausal women and dividing the subject's ages to <50 and >50 years [4,22]. It has been demonstrated that menopause and age >50 years is a risk factor for the occurrence of osteopenia and osteoporosis [6,21]. According to previous studies, the age distribution of menopause ranges from 40 years to 54 years and generally clusters at the age of 45 to 55 years [23].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Based on the age-cutting value of the ROC curve, the majority of subjects were aged >54.50 years (Table 2), which agrees with the study of postmenopausal women and dividing the subject's ages to <50 and >50 years [4,22]. It has been demonstrated that menopause and age >50 years is a risk factor for the occurrence of osteopenia and osteoporosis [6,21]. According to previous studies, the age distribution of menopause ranges from 40 years to 54 years and generally clusters at the age of 45 to 55 years [23].…”
Section: Discussionsupporting
confidence: 82%
“…Body mass index (BMI) is an inexpensive and simple method for assessing an individual's nutritional status but it does not directly measure body fat. Measurements and assessments using BMI are associated with deficiency and excess nutritional status [6].…”
Section: Introductionmentioning
confidence: 99%
“…In the proximal segment, a high percentage of low BMD is particularly worrying also in the same groups of boys (in 70.6% of non-athletes and 83.3% of swimmers). Among children [ 47 ], young adults [ 14 , 17 , 48 ], and physically inactive adults and older adults [ 6 , 10 ], the frequency of low BMD is higher than in peers undertaking regular PA. On the other hand, not all types of physical exercise and forms of movement have shown positive effects on BMD and BMC. Swimming training improves mental health parameters, cognitive abilities and motor coordination of children and adolescents [ 49 ], but at the same time does not produce osteogenic benefits [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relationships between bone health and body composition are sometimes contradictory [ 15 ]. In the adult population, BMD often shows a stronger correlation with the body mass index (BMI) and lean body mass, and much smaller with body fat mass [ 16 , 17 ]. Some studies of healthy mature adolescents and young adults have shown that high levels of adipose tissue are not beneficial for bone structure [ 18 ] or show no significant relationship [ 12 ].…”
Section: Introductionmentioning
confidence: 99%